MNGI-09. MENINGIOMA WITH MULTIPLE DRIVERS: GENOMIC LANDSCAPE AND CLINICAL CORRELATIONS. (11th November 2019) - Li, Chang; Tyrtova, Evgeniya; Youngblood, Mark; Miyagishima, Danielle; Duran, Daniel; Montejo, Julio; Özduman, Koray; Sheth, Amar; Zhao, Amy; Fomchenko, Elena; Clark, Victoria; Sohrabi, Sadaf; et al.
Abstract: BACKGROUND: Previous studies have established several meningioma genomic subgroups, defined by the mutually exclusive genomic drivers. However, we distinguished a small subset of meningiomas simultaneously harboring multiple drivers from different genomic subgroups, thus referred to as "multiple-driver meningiomas", that has not been previously investigated. We aimed to characterize the genomic landscape and clinical features of multiple-driver meningiomas. METHODS: We identified 42 cases of multiple-driver meningiomas from a cohort of 3, 016 cases screened for genomic drivers via molecular inversion probe sequencing (MIPS) and/or whole-exome sequencing (WES) previously in our laboratory. All driver mutations were validated via Sanger sequencing and chromosome 22 loss was accessed with qPCR. Clinical information was collected and genome-to-clinical correlations were statistically analyzed. We selected 10 multiple-driver meningioma cases for tumor-normal WES for further characterization of genomic architecture. RESULTS: Multiple-driver meningiomas were significantly enriched for NF2 alteration (p< 0.001), had significantly higher WHO grade (p= 0.005) and proportion of recurrent tumors (p= 0.007) when compared with "single-driver meningiomas", i.e. harboring driver alterations from a single genomic subgroup. Among female cases, those with multiple drivers were nearly four times more likely to be high-grade (II or III) compared to single-driver female samples (48.6% vs. 12.6%, p< 0.001). Among tumors harboring NF2 alteration, multiple-driver meningiomas demonstrated skull base predilection compared with single-driver meningiomas (50.0% vs. 27.9%, p= 0.005). WES analysis of 10 multiple-driver meningiomas identified 1p and/or 14q loss in 60% of cases. Clonality analysis revealed the presence of sub-clonal cell populations in 9 cases with all driver mutations clustered into the founding clone in 7 cases, suggesting their acquisition in the early phase of tumor development. CONCLUSION: Multiple-driver meningiomas demonstrate distinct genomic and clinical features that distinguish them as clinically aggressive. They frequently occur in surgically challenging skull base locations, and are more prevalent among high-grade and recurrent cases.